2015
DOI: 10.1145/2786566
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Dimension

Abstract: We define the lower and upper mutual dimensions mdim(x : y) and Mdim(x : y) between any two points x and y in Euclidean space. Intuitively, these are the lower and upper densities of the algorithmic information shared by x and y. We show that these quantities satisfy the main desiderata for a satisfactory measure of mutual algorithmic information. Our main theorem, the data processing inequality for mutual dimension, says that if f : R m → R n is computable and Lipschitz, then the inequalities mdim( f (x) : y)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…where dim H (E) is the (classical) Hausdorff dimension of E, i.e., the most standard notion of fractal dimension. Although (1) does not hold in general, this correspondence suggested that effective dimensions might provide new techniques for dimension bounds in classical fractal geometry. A recent point-to-set principle of J. Lutz and N. Lutz [14] reinforces that prospect by characterizing the Hausdorff dimension of arbitrary sets in terms of effective dimension.…”
Section: Introductionmentioning
confidence: 99%
“…where dim H (E) is the (classical) Hausdorff dimension of E, i.e., the most standard notion of fractal dimension. Although (1) does not hold in general, this correspondence suggested that effective dimensions might provide new techniques for dimension bounds in classical fractal geometry. A recent point-to-set principle of J. Lutz and N. Lutz [14] reinforces that prospect by characterizing the Hausdorff dimension of arbitrary sets in terms of effective dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The theorem follows directly from the properties of mutual dimension between points in Euclidean space found in [4] and the correspondences described in corollaries 2.5, 2.6, and 2.14.…”
Section: Lemma 24mentioning
confidence: 90%
“…The objects x and y of interest in [4] are points in Euclidean spaces R n and their images under computable functions, so the fine-scale geometry of R n plays a major role there.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the dimension spectrum of a line L a,b ⊆ R 2 may properly contain the unit interval described in our main theorem, even when dim(a, b) = Dim(a, b). If a ∈ R is random and b = 0, for example, then sp(L a,b ) = {0} ∪ [1,2]. It is less clear whether this set of "exceptional values" in sp(L a,b ) might itself contain an interval, or even be infinite.…”
Section: Future Directionsmentioning
confidence: 99%